The relationship between caregiver burden and hope in leukemia patients: a cross-sectional study in selected referral hospitals in Tehran, Iran - Azam Ghorbani; Moein Salami; Mohammad Mehdi Rajabi (BMC Palliative Care)
Abstract Background Leukemia is a life-threatening condition that imposes significant challenges not only on patients but also on their caregivers. Caregiver burden, a multidimensional concept encompassing physical, psychological, and emotional strain, often impacts the quality of care provided to patients. Conversely, hope, a critical psychological resource, plays a pivotal role in patient well-being and coping. Understanding the relationship between caregiver burden and patient hope is essential for improving holistic cancer care. Methods This descriptive correlational study was conducted at the Cancer Institute and Valiasr Hospital, affiliated with Tehran University of Medical Sciences, between May and November 2024. A total of 400 participants, including 200 leukemia patients and their 200 primary caregivers, were recruited using convenience sampling. Data were collected using the Zarit Caregiver Burden Interview (ZBI) and Snyder’s Adult Hope Scale (AHS). Descriptive statistics and Pearson’s correlation coefficient were used to analyze the data in SPSS version 16, with a significance level of P < 0.05. Results The mean caregiver burden score was 37.69 ± 7.12, indicating a moderate level of burden, while the mean hope score among leukemia patients was 32.19 ± 1.88, reflecting relatively high levels of hope. A weak but statistically significant negative correlation was found between caregiver burden and overall hope scores (r= -0.164, P = 0.02). However, no significant correlations were observed between caregiver burden and the subscales of hope, namely Pathway Thinking (r=-0.127, P = 0.073) and Agency Thinking (r=-0.126, P = 0.076). Conclusion The study highlights a significant inverse relationship between caregiver burden and patient hope, underscoring the interconnected dynamics between caregiver well-being and patient psychological resilience. Interventions aimed at reducing caregiver burden and fostering hope in patients are essential for enhancing the overall quality of care in leukemia. Clinical trial number Not applicable.